Pengaruh Store Atmosphere, Diskon Harga dan Lokasi Terhadap Keputusan Pembelian di KFC Toraja - Ashary Bungin; Mince Batara; Helba Rundupadang (CV. Ulil Albab Corp, 2024)
This research aims to test and determine the influence of store atmosphere, price discounts and location on purchasing decisions at KFC Toraja. The research method uses quantitative research. The data collection technique was through a questionnaire. The population in this study were all consumers who visited KFC Toraja and the sample used used an accidental sampling technique, which means anyone who received the questionnaire and matched the criteria could be used as a sample. Data were analyzed using the SPSS 16 program. The results of this research show that, partially, the store atmosphere value has an influence but is not significant on purchasing decisions at KFC Toraja, price discounts do not significantly influence purchasing decisions at KFC Toraja, and location influences purchasing decisions at KFC Toraja. And simultaneously the results show that the three variables, namely store atmosphere, price discounts and location together have a significant influence on purchasing decisions